(untitled) (Research, Society and Development, 2022)
Collagen biostimulators are facial fillers that have the ability to act in the deeper portions of the skin, stimulating collagen production through localized subclinical inflammatory responses. They are considered safe materials because they have characteristics such as biocompatibility, biodegradation, production of minimal adverse effects, and satisfactory results. The aim of this article is to analyze the types and properties of semi-permanent stimulators available in the market, as well as their mechanisms of action, duration of effects, indications and contraindications. This is an integrative literature review, and articles from the last 5 years, related to the subject were searched in the PubMed, LILACS, Scielo and Google Schoolar databases with the following descriptors: (dermal fillers) AND (calcium hydroxyapatite); (dermal fillers) AND (poly l lactic acid); Sculptra; (dermal fillers) AND (polycaprolactone). By providing facial rejuvenation, treating expression lines and also promoting a filling of the face volume, allowing an improvement in the support and firmness of the skin, these materials are being preferred to invasive procedures such as plastic surgery.